1991
DOI: 10.1002/dvg.1020120111
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐cell contact mediates cAMP secretion in Dictyostelium discoideum

Abstract: Cyclic adenosine 3':5' monophosphate (cAMP) and cell-cell contact regulate developmental gene expression in Dictyostelium discoideum. Developing D. discoideum amoebae synthesize and secrete cAMP following the binding of cAMP to their surface cAMP receptor, a response called cAMP signaling. We have demonstrated two responses of developing D. discoideum amoebae to cell-cell contact. Cell-cell contact elicits cAMP secretion and alters the amount of cAMP secreted in a subsequent cAMP signaling response. Depending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…1992). Since the formation of cell–cell contacts affects cAMP metabolism and cAMP signaling (Fontana & Price 1988; Fontana et al. 1991a,b), it is possible that the loss of DdCAD‐1 expression may somehow enhance cAMP signaling and stimulate a higher level of csA/gp80 expression.…”
Section: Regulation Of Temporal Expression Of Camsmentioning
confidence: 99%
“…1992). Since the formation of cell–cell contacts affects cAMP metabolism and cAMP signaling (Fontana & Price 1988; Fontana et al. 1991a,b), it is possible that the loss of DdCAD‐1 expression may somehow enhance cAMP signaling and stimulate a higher level of csA/gp80 expression.…”
Section: Regulation Of Temporal Expression Of Camsmentioning
confidence: 99%
“…In addition to intercellular adhesion, there is increasing evidence that the classic cadherins are involved in signal transduction (72). In Dictyostelium, several recent reports have shown that cell-cell contact can elicit cAMP secretion and modulate cAMP signaling in Dictyostelium (73)(74)(75). Recent studies in our laboratory have demonstrated a role for cell-cell contact in a cAMP-dependent pathway that regulates gene expression, as well as in the cAMP signal relay system (19).…”
mentioning
confidence: 99%
“…Several recent reports suggest that an interdependent relationship exists between cell-cell contact and cAMP signaling [15][16][17]. We have previously shown that cellcell contact is required for the stimulation of csaA expression [10].…”
Section: Cada Expression Was Not Influenced By Cell-cell Contactmentioning
confidence: 99%